Evaluation of the Relationship Between Hand Osteoarthritis and Osteoporosis in Postmenauposal Women - Oya Özdemir; Fitnat Dinçer; Gülbüz Samut (Galenos Yayinevi, 2013)
Aim: Osteoarthritis (OA) and osteoporosis (OP) are the two leading causes of disability in elderly. The aim of this study was to compare the values of bone mineral density (BMD) in postmenopausal women with and without hand OA. Meterial and Methods: 26 patient with hand OA and 22 age and sex-matched individuals without hand OA were included in the study. The patients with secondary OP and under the treatment of OP were excluded. In physical examination, the number of tender and swollen joints, Heberden and Bouchard nodules were recorded. The participants' grip and lateral pinch strength were measured using Jamar dynamometer and pinchmeter. The Australian Canadian Osteoarthritis Hand Index (AUSCAN) was used to evaluate pain and function. Additionally, the pain during rest and activity were evaluated on a 10-cm visual analog scale (VAS). BMD was measured from 3 different regions (femur neck, lumbar vertebra, and radius) using dual energy X-ray absorptiometry. Results: The mean age of the patients' was 59.0±6.1 years and 84.6% were right-handed. No signi cant difference was found in BMD values of the femur neck, lumbar vertebra between the two groups. However, the patients with hand OA had signi cantly lower t-scores of distal radius (p=0.045). There was no statistically signi cant correlation between distal radius t-score and age, body mass index, postmenopausal duration, right hand pinch strength, number of nodules in the right hand, pain duration, VAS rest and activity scores, AUSCAN pain, stiffness and function scores whereas we found a positive correlation between distal radius t-score and right hand grip strength in the patient group (r=0.478, p=0.016). Conclusion: Several studies investigating the relationship between hand OA and OP found positive correlation whereas some found negative correlation. We found an inverse relationship between hand OA and distal radius t-score. Further studies are needed to enlighten the pathogenesis of this relationship. (Turkish Journal of Osteoporosis 2013;19: 1-6)